Autonomia e responsabilità medica: la scelta deontologicamente (dis)orientata (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
Starting from the difficulties in balancing the need for certainty with flexibility in the regulation of medical practice, the paper analyses the role of medical ethics in defining, safeguarding and governing medical autonomy and responsibility. Convergences, divergences and mutual relationships between professional ethics and law are discussed, with consideration and evaluation of the challenges the role of this source of (soft)law is facing. Reflecting upon a more broader context of medical responsibility, which does not simply correspond to legal liability, the aim of this paper is, on the one hand, to clarify the framework for the potential but controversial role of the code of medical ethics, and on the other hand, to highlight specific elements and devices that should be taken into consideration in shaping a more coherent model of relationships between law, scientific evidence and medical ethics.
Keywords: Code of medical ethics; medical autonomy; medical responsibility; biolaw; scientific evidence